THE EFFECT OF LEARNING STYLE ON THE ABILITY TO WRITE NARRATIVE TEXT AT SENIOR HIGH SCHOOL 4 GRESIK - Dianita Dwi Jayanti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study tries to investigate the differences in students' abilities to write narrative texts associated with their learning styles. To achieve this purpose, an ex-post facto design was employed with 62 students of grade 9 at Senior High School 4 Gresik being used as the subjects of the study. A questionnaire was used to group the students based on their learning style preferences into audio, visual, and kinesthetic styles. In addition, a test of writing was designed to collect the data of the students’ ability to write narrative texts. The collected data were then analysed using One-Way ANOVA and it was found that F-value was 5.469 (p=.007). This indicates that students with audio, visual, and kinesthetic learning styles have significantly different ability to write narrative texts. It was also found that students with visual learning style had the highest score in writing narrative texts, while students with audio learning style had the lowest score. Keywords: learning style (visual, audio, and kinesthetic) and narrative writing skill